Synthesis of silver nanoparticles deposited in porous ceramic by γ-irradiation - Du, Bui Duy; Ai Trinh, Nguyen Thuy; Thang, Ngo Manh; Kim Lan, Nguyen Thi; Phu, Dang Van; Hien, Nguyen Quoc (Vietnam Journal of Chemistry, 2015)
Silver nanoparticles (Ag nano) were deposited in porous ceramic (PC) that was functionalized with aminosilane (AS) agent (PC-AS-Ag nano) by gamma Co-60 irradiation of the PC-AS/Ag+ mixture using polyvinylpyrrolidone (PVP) as stabilizer. Effect of dose on the formation of Ag nano was investigated. Characteristics of the nanocomposite material (PC-AS-Ag nano) were determined by ultraviolet visible spectroscopy (UV-Vis), X-ray diffraction (XRD), transmission electron microscopy (TEM) and inductively coupled plasma-atomic emission spectroscopy (ICP-AES). Results indicated that Ag nano size was 9 nm and the Ag nano content in PC-AS-Ag nano material was about of 341 ± 51 mg/kg at dose of 14-20 kGy. Thus, gamma Co-60 irradiation method has the advantage of creation of small Ag nanoparticles with fairly homogenous distribution in PC material.